Internet traffic prediction using kernel online learning - Che, Jiuwei (2014)
Nowadays, with the development and popularity of network, internet has been widely used around the world. To satisfy the demand for the network, we need to supply the flow more efficiently. In this case, we aim to come with a manner to predict the future internet traffic accurately.